Pemberdayaan Perempuan Pengrajin Batik Papua Melalui Pendekatan Pendidikan Berbasis Kearifan Lokal: Studi Kasus Pada Sanggar Asasilen Di Kampung Nafri Kota Jayapura - siti fatimah; Andika Dian Saputra (Jurnal at-Taghyir: Jurnal Dakwah dan Pengembangan Masyarakat Desa, 2026)
Women's empowerment has become an important strategy for promoting socio-economic development while preserving local cultural heritage. This study examines the empowerment of Papuan women batik artisans through a local wisdom-based educational approach at Asasilen Batik Studio in Jayapura Regency, Papua. The research was conducted due to the limited educational support available to women artisans despite their significant contribution to cultural preservation and family welfare. A qualitative case study approach was employed, involving in-depth interviews, observation, and documentation with the studio leader and members as key informants. Data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that women's empowerment is implemented through batik training, business mentoring, and the transmission of cultural knowledge embedded in traditional Papuan motifs. Local wisdom-based education is integrated into the learning process by introducing the philosophical meanings of motifs such as bows and arrows, tifa drums, and fishbone patterns, which reflect indigenous values and cultural identity. Supporting factors include government assistance, community support, and strong motivation to preserve local culture, while challenges involve limited access to raw materials and social issues related to the use of traditional motifs. The study further indicates that participation in batik production has improved women's economic capacity, self-confidence, social participation, and cultural awareness. These findings demonstrate that local wisdom-based education can serve as an effective model for empowering women while ensuring the sustainability of Papuan cultural heritage.